2017
DOI: 10.1111/joa.12753
|View full text |Cite
|
Sign up to set email alerts
|

Development of the human shoulder joint during the embryonic and early fetal stages: anatomical considerations for clinical practice

Abstract: Although several studies have been published regarding the morphology and anatomical variations of the human shoulder joint, most have dealt with adult individuals. Those looking into the development of the joint have been focused on specific structures or have observed specimens in advanced gestational stages. The goal of this paper is to perform a complete analysis of the embryonic and early fetal development of the elements in the shoulder joint, and to clarify some contradictory data in the literature. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…Mekonen et al detected the scapula (shoulder blade) at CS17 in histological sections [29]. Hita-Contreras et al observed the chondrogenic anlagen at the medial border of the scapula from as early as CS17, whereas the scapula body appeared at CS18 [10]. We first detected the scapula body at CS17 with the coracoid and humeral head at CS18 on PCX-CT images, consistent with recent histological studies.…”
Section: Plos Onesupporting
confidence: 89%
See 2 more Smart Citations
“…Mekonen et al detected the scapula (shoulder blade) at CS17 in histological sections [29]. Hita-Contreras et al observed the chondrogenic anlagen at the medial border of the scapula from as early as CS17, whereas the scapula body appeared at CS18 [10]. We first detected the scapula body at CS17 with the coracoid and humeral head at CS18 on PCX-CT images, consistent with recent histological studies.…”
Section: Plos Onesupporting
confidence: 89%
“…In this study, the connection of the body and coracoid could not be confirmed at CS18 because of the resolution of the PCX-CT image. Hita-Contreras et al observed three outgrowths of the mesenchymal condensation with an irregular shape corresponding to the body of the scapula, future coracoid process, and large mass of the humerus, acromion, and spine of the scapula [10]. The authors, however, did not mention whether these three outgrowths were connected.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the concerns address the anterior part of the cable that ends in the region of the rotator interval, interweaving with the coracohumeral and superior glenohumeral ligaments (Choo et al 2014; Kask et al 2008; Kolts et al 2000; Pouliart et al 2007). Embryological studies report only that the development of the glenohumeral joint capsule occurs during Carnegie stages 22–23 (Aboul-Mahasen and Sadek 2002; Fealy et al 2000; Hita-Contreras et al 2017). However, as it has been reported in macroscopic (Burkhart et al 1993; Rahu et al 2016) and microscopic (Fallon et al 2002) studies, and as we confirmed in normal and pathological specimens, rotator cables form a functional complex with the supra- and infraspinatus muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis by Hita-Contreras et al (2018) has shown that this mesenchymal condensation has multiple outgrowths: one each for the scapular body, coracoid process, and the acromion and spine. These findings agree with Capellini et al (2010) assessment using 3D Optimal Projection Tomography of the boundaries of Sox9 expression, a marker of mesenchymal condensation formation.…”
Section: Scapula Developmentmentioning
confidence: 99%